DFT Study on Ce-Doped Anatase TiO2: Nature of Ce3+ and Ti3+ Centers Triggered by Oxygen Vacancy Formation - Albuquerque, Anderson R. [UNESP]; Bruix, Albert; Santos, Ieda M. G. dos; Sambrano, Julio R. [UNESP]; Illas, Francesc (Amer Chemical Soc, 2014)
A systematic study of TiO2 anatase, Ce-doped TiO2 anatase with 2.8 and 5.6% dopant concentration and of the systems resulting from oxygen vacancy formation has been carried out by means of periodic density functional theory based calculations using PBE, PBE+U, and hybrid functionals. For each approach, several situations are considered for the oxygen vacancy formation, differing on the position of the removed oxygen or on the resulting electronic structure. The hybrid B3LYP functional and PBE+U approaches provide a physically meaningful description of localized d and f electrons in Ti3+ and Ce3+ species, respectively. Nevertheless, quasi-degenerate solutions were encountered featuring either fully localized spin (simple and split) or partially localized spin. Although standard PBE calculations result always in fully (unphysical) delocalized solutions, the most stable geometry thus predicted, in which Ce is six-coordinated and V-O folded by 3[TiO5], is in agreement with the B3LYP and PBE+U results. The present work provides compelling evidence that the remarkable catalytic properties of these systems partially arise from the facilitated oxygen vacancy (V-O) formation triggered by the Ce dopant, which is further enhanced when dopant concentration is increased.